2014
DOI: 10.5120/15339-3674
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method of Number Plate Extraction from Indian Vehicles Image

Abstract: Automatic Number Plate Recognition (ANPR) is an imageprocessing technology that identifies vehicles by their number plates without direct human intervention. It is an application of computer vision and important area of research due to its many applications. The main process of ANPR is divided into four stages. This paper presents a simple and efficient method for the extraction of number plate from the vehicle image based on morphological operations, thresholding and sobel edge detection, and the connected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…Initially image is captured by high quality camera then preprocessing of captured image is performed to reduce the unwanted signals present in the image. In next step the image is converted from RGB to gray scale image based on the threshold value [11].…”
Section: Image Preprocessingmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially image is captured by high quality camera then preprocessing of captured image is performed to reduce the unwanted signals present in the image. In next step the image is converted from RGB to gray scale image based on the threshold value [11].…”
Section: Image Preprocessingmentioning
confidence: 99%
“…One of the best filter, which is widely used in the ANR system is Median filter [5][8] [9]. Sarbjit Kaur and Sukhvir Kaur [11] suggested that, Noise also can be removed by using Iterative bilateral filter [11] in ANR Domain. In [19] they have proposed to blur the image in order to remove the noise.…”
Section: Noise Removalmentioning
confidence: 99%
See 3 more Smart Citations